Analisis sektor-sektor ekonomi Provinsi Jambi - Harry Gunawan Putra; M. Syurya Hidayat; Erni Achmad (e-Jurnal Perspektif Ekonomi dan Pembangunan Daerah, 2015)
This study aims to analyze: (1) the development of GRDP and economic sectors in Jambi Province; (2) a shift in economic sectors in the structure of the economy in Jambi Province; (3) base sector in Jambi Province; (4) typology of growth in the base sector in the economy in Jambi Province. The data used are secondary data from Jambi Province during the period 2000 - 2012. Data is sourced from the Central Bureau of Statistics of Jambi Province and the Bappeda of Jambi Province. The analytical tool used is shift share analysis, Location Quotient and typology of Klassen. The results of the study indicate that: (1) the average development of the GRDP of Jambi Province during the period 2000-2012 was 6.43 percent. The economic sector with the highest development is the finance, leasing & business services sector, and the smallest sector of economic development is the services sector; (2) the average contribution of the primary sector to the GRDP of Jambi Province during the period 2000-2012 was 43.49 percent, the secondary sector was 35.36 percent and the tertiary sector was 21.15 percent; (3) the base or superior sector in Jambi Province during the period 2000-2012 was the agricultural sector, mining & quarrying sector, electricity, gas & clean water sector, trade, hotel & restaurant sector and transportation & communication sector; (4) Jambi Province is categorized as a developed region and is growing rapidly. The sectors that are categorized as advanced and rapidly growing sectors are the agricultural industry sector, mining & quarrying sector, electricity, gas & water, construction sector, trade, hotel & restaurant sector and services sector. The sector that is categorized as an advanced but depressed sector is the transportation & communication sector. The sectors categorized as potential sectors are the manufacturing industry sector, and the financial, leasing & business services sector.